VACCINATION AGAINST CORONAVIRUS INFECTION IN UZBEKISTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
WHO has announced the Covid-19 pandemic, which has spread throughout the world. Vaccination is the only way to fight this infection. On April 1, the process of vaccination of the population against coronavirus began in Uzbekistan.Three vaccines are used in the Republic of Uzbekistan (ZF-UZ-VAC 2001, Astra Zeneca and SPUTNIK '' V ''). The article describes the vaccination coverage of citizens of Uzbekistan at stage 1 for the period from April 1 to May 7